Retinol, proteínas transportadoras, carotenóides, proteínas de fase aguda e barreira funcional intestinal em crianças de uma comunidade urbana de Fortaleza - Vieira, Milena Morais (2007)
Vitamin A deficiency (VAD) is considered an important public health problem worldwide and the role of VAD on intestinal epithelial integrity is not well understood. To investigate the association of retinol (vitamin A) and carotenoids with the intestinal barrier function from children in an urban community in Fortaleza, Northeastern Brazil, one hundred and two children from 2 months to 9 years old participated in the study. The nutritional status of these children, measured by weight for height z-score (WHZ), showed that 19.6% (20/102) of them had mild malnutrition (-1 to –2 z-score). All children had their serum retinol concentration measured and none were severely deficient (<= 0.35 µM), 2.9% (3/102) were moderately (0.36 – 0.70 µM), 20.6% (21/102) were mildly (0.71 – 1.05 µM) deficiencies; 76.5% (78/102) were vitamin A sufficient (> 1.05 µM). The lactulose:mannitol (L/M) ratio was abnormal in 49% (47/97) of children when compared to healthy children in the same geographic area. Serum carotenoids, lutein, beta-cryptoxanthin and beta-carotene showed significant inverse correlation with the L/M ratio. Acute phase proteins (C-reactive protein; CRP; and α-acid glycoprotein; AGP) were significantly inversely correlated with retinol. Retinol was significantly correlated with retinol-binding protein (RBP), and with transthyretin (TTR). These data suggest a disruption of intestinal barrier function due to paracellular pathway with low serum concentrations of carotenoids. The retinol precursors, carotenoids, may provide a better marker for disrupted intestinal barrier function than measurements of RBP or retinol. Serum retinol concentrations correlate with RBP and TTR and inversely correlate with AGP and CRP